PREFERENSI WISATAWAN NUSANTARA MEMILIH HOTEL BERBINTANG DI DAERAH ISTIMEWA YOGYAKARTA - Fajri, Devy Dwi; J. Damanik, J. Damanik (Profit: Jurnal Adminsitrasi Bisnis, 2020)
In recent years, there is significant increase of hotel industry in Daerah Istimewa Yogyakarta (DIY), specifically star hotel. The room growth of star hotel from 2014-2018 continuously increases. Based on hotels’ Room Occupancy Rate (ROR), star hotels averagely have higher ROR compared to the non star ones. It shows that star hotels’ market segment is potential to be developed. Thus, the approach from tourists’ side is needed to find out what factors that influence or distinguish tourist preference who use star hotels. Survey is applied as the method to figure out tourist preference. The study focuses on the number of tourists who use star hotel, here is a domestic tourist. The result shows that based on the age, gender, occupation, travel type of domestic tourists there are differences of their preference in service, main facility (room), and additional hotel facility. Afterwards, based on the origin, there is no difference of preference found in tourist attraction choices and length of stay from domestic tourists towards location, service, main facility, and additional hotel facility choices. The findings are expected to give feedbacks for hotel managers in determining strategic steps of star hotel development in order to be sustainable.